The Infallibility of the prophets and their Adjectives in the Holy Quraan in theought of two Allamas Shihabuldin AL-ALousi and Muhammed Hussain AL-Tabatabaie Comparative Study (Journal of the College of Basic Education, 2022)
The nature of this study has included an introduction, three Chapters, and a conclusion. In the foreground, I have mentioned the reason for choosing this topic, Concerning the first chapter which is titled "profiles of the two Allams AL-ALoussi and AL-Tabatabaie and their concept of thought of prophet and Messenger". Also, there are three types of research and a collection of requirements. In the first research, I explained "the life of the Allams AL-Aloussi and his curriculum vitae". In the second research "the life of the Allams AL-Tabatabaie and his curriculum vitae". In this research, I showed the concept of thought, prophet, and Messenger both in language and terms with the point of view of the two Allams mentioning the difference between the prophet and the Messenger. The second chapter that is titled "the concept of the infallibility and their aspects and evidence in the thought of the two Allams" . This chapter included two types of research and several requirements, where I searched in the first research "concept of infallibility and its reference in the thought of the two Allams". In the second topic, I explained "the concept of the aspects and its references in the thought of the two Allams. Whereas the third chapter is titled "Quranic verse" which includes the infallibility of prophets "peace of God be upon them" due to the thought of the two Allamas AL-Aloussi and AL-Tabatabaie. This chapter comprises three types of research and a collection of requirements, In the first research "Quranic verses" comprising the infallibility of prophets "peace and prayers upon them" with "first determined" such as the prophet Adam, prophet Yousif, prophet Yunus, prophet Dawood and the prophet Ayub. The second study is "Quranic verses included the infallibility of the prophet "peace be upon them" and the "first determined" without the prophet Muhammed "peace be upon him and his family", in addition to "definition of first determined" in the language in term comprising (their nomination and their number) mentioning "the prophet Nouh, prophet Ibrahim, prophet Mussa and prophet Jesus (peace be upon them all). In the third study "the Quranic verses comprising the infallibility of the most generous prophet Muhammed "peace be upon him and his family" in addition to "the definition of the prophet Muhammed "peace be upon him and his family" such as (his description and personality). Then in the conclusion, I try to show what I got in this topic from the results and conclusion. Finally, I'd like to confess that my study is just a curriculum matter and I can't dare to say that, through my study, I gave enough knowledge that concerns the two Allamas AL-Allousi and Tabatabaie. On the other hand Iam very proud to go all my best to produce an important and vital topic. On this occasion, we ask God and pray to Him to grant us the well–being of all.